1981
DOI: 10.1159/000131571
|View full text |Cite
|
Sign up to set email alerts
|

Somatic pairings of the Y heterochromatin in human XYY and XYqi cells

Abstract: In human interphase nuclei containing Yq isochromosomes or two Y chromosomes, there are conspicuous somatic pairings between the brightly fluorescing Y-heterochromatin regions. These somatic pairings cannot be demonstrated in metaphases from conventional cell cultures because they are disrupted at the mitotic prophase. However, in lymphocytes cultivated in a medium containing distamycin A, the somatic pairing between Y-heterochromatin is preserved to metaphase. The present findings are compared with earlier ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Firstly, the results of statistical analysis of chromosome arrangements at metaphase are compared with the results of chromosome arrangements at interphase obtained with the microbeam or other independent methods (Schmid et al 1981;Dutrillaux et al 1981;Hager et al 1982;Hens et al 1982). The variability of interphase chromosome arrangements as indicated by the present microbeam study is in agreement with the variability of chromosome positions and the lack of association between homologous chromosomes in the metaphase spread.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Firstly, the results of statistical analysis of chromosome arrangements at metaphase are compared with the results of chromosome arrangements at interphase obtained with the microbeam or other independent methods (Schmid et al 1981;Dutrillaux et al 1981;Hager et al 1982;Hens et al 1982). The variability of interphase chromosome arrangements as indicated by the present microbeam study is in agreement with the variability of chromosome positions and the lack of association between homologous chromosomes in the metaphase spread.…”
Section: Discussionsupporting
confidence: 75%
“…Recent studies of the distribution of interphasic centromeres indicate considerable variation in cell types from different plant and mammalian species (Church and Moens 1976;Del Fosse and Church 1981;Moroi et al 1981;Brenner et al 1981). Thirdly, and probably most important, the technical procedures routinely used for obtaining well spread metaphases (often including colchicine treatment and hypotonic shock) alter the chromosome arrangement of the intact metaphase plate to an extent which has not been documented by most investigators, although it can be shown that the relationship between chromosome arrangements at interphase and metaphase is critically influenced by the experimental regimen followed (Schmid et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the C-bands of chromosome 1, 9 and 16, the noncentric C-band of the Y chromosome is almost unaffected in normal cells on MMC-treatment (Shaw and Cohen, 1965;Morad et al, 1973), despite a comparable size of the C-bands (Joseph et al, 1982b). However, in lymphocytes from a XYY male patient MMC treatment resulted in a frequent involvement of the Y chromosomes in interchanges, almost exclusively in Y-Y configurations (Schmid et al, 1981;Joseph et al, 1982b). Hence it is clear that also the C-band of chromosome Y is susceptible to MMC ICLs, but that sequence homology is required for a subsequent formation of chromosome interchanges.…”
Section: Discussionmentioning
confidence: 99%
“…9 in human interphase nuclei can be observed by means of the Giemsa-ll-staining procedure (Gagn6 and Laberge 1972;Spaeter 1975). Another example concerns the position of the heterochromatic sex chromosomes forming large chromocenters in interphase nuclei of Microtus agrestis (Pera and Schwarzacher 1970), while the position of the human Y-heterochromatin can be identified by quinacrine mustard staining (Pearson et ah 1970;Schmid et al 1981).…”
Section: Introductionmentioning
confidence: 99%